2014
DOI: 10.1097/01.tp.0000437561.31212.0e
|View full text |Cite
|
Sign up to set email alerts
|

Lower Variability in 24-Hour Exposure During Once-Daily Compared to Twice-Daily Tacrolimus Formulation in Kidney Transplantation

Abstract: Intrapatient CV of Tac AUC0-24 improved after converting from Tac BID to Tac QD in stable renal transplant patients, especially in patients with the CYP3A5*1/3 genotype. Given the very strict protocol of this PK study, this improvement is most likely due to the different intrinsic PK properties of Tac QD and Tac BID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
97
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 15 publications
6
97
2
4
Order By: Relevance
“…In the EVOLUTION study (EValuation Of Advagraf conversion and Long-term Use in kidney TransplantatION), for example, a 34% improvement in adherence to tacrolimus was observed in the patients receiving the prolonged-release versus immediate-release formulation. 79 These findings were consistent with Stifft et al 77 who reported a 23% reduction in intrapatient variability after conversion from immediate-to prolonged-release tacrolimus. Previously published studies have also demonstrated a lower variability of tacrolimus exposure and improved adherence to treatment with prolonged-release versus immediate-release tacrolimus.…”
Section: Underimmunosuppression In Kidney Transplantationsupporting
confidence: 82%
See 3 more Smart Citations
“…In the EVOLUTION study (EValuation Of Advagraf conversion and Long-term Use in kidney TransplantatION), for example, a 34% improvement in adherence to tacrolimus was observed in the patients receiving the prolonged-release versus immediate-release formulation. 79 These findings were consistent with Stifft et al 77 who reported a 23% reduction in intrapatient variability after conversion from immediate-to prolonged-release tacrolimus. Previously published studies have also demonstrated a lower variability of tacrolimus exposure and improved adherence to treatment with prolonged-release versus immediate-release tacrolimus.…”
Section: Underimmunosuppression In Kidney Transplantationsupporting
confidence: 82%
“…Previously published studies have also demonstrated a lower variability of tacrolimus exposure and improved adherence to treatment with prolonged-release versus immediate-release tacrolimus. 76,77,80 Previously reported data from 40 000 patients over 6 years of follow-up suggest that there is an annual decrease in renal function in the posttransplant period of~1.6 mL/min per 1.73 m 2 per year, 81 with similar findings being reported for 4000 kidney transplant patients in the Catalan Registry (−1.5 mL/min per 1.73 m 2 per year). These data suggest that even 'stable' patients are experiencing a decline in renal function over time and that we need to continue to monitor this decline and to modify our therapeutic regimens to improve outcomes for our patients.…”
Section: Underimmunosuppression In Kidney Transplantationsupporting
confidence: 71%
See 2 more Smart Citations
“…151,154 The conversion from twice-daily to prolonged-release tacrolimus (capsules), both in kidney and liver transplant recipients, leads to lower blood trough concentrations and a reduced IPVof tacrolimus. 155,156 In a single study performed in liver transplant recipients, the early conversion to prolonged-release tacrolimus capsules was accompanied by a significant reduction of TCMR rates. 114 It remains unclear, however, whether a reduction in IPV motivated by conversion to prolonged-release tacrolimus capsules would also lead to improved clinical outcomes; prospective trials are needed.…”
Section: Highly Modifiable Contributors To Variabilitymentioning
confidence: 99%